Charitable activities of Russian companies - Davydenko, Elena (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article analyzes the activities of charitable organizations in Russia. The author explores the motives for carrying out charitable activities. Based on the results of the in-depth interview, the priority areas for the activities of charitable organizations in Russia, the requirements that the state should establish in relation to charitable organizations, as well as the specifics of interaction between the state and charitable organizations, are determined. The article also explores the fundamentals of legislative regulation of charitable activities in Russia.
Keywords: organizacje charytatywne; działalność charytatywna; państwo; zasiłki; ludność